ANALISIS WACANA FOUCAULT DALAM STUDI KOMUNIKASI - Holy Rafika Dhona (Journal Communication Spectrum, 2019)
Michel Foucault is a popular thinker across disciplines in academia. In Indonesian communication studies, his concepts are used in several ways as an instrument analysis on many communications' act/ event. The problem is only little, or even no one, wrote how to do the Foucauldian method of analysis in the context of communication studies. This article proposes how to do Foucauldian analysis in communication studies by focusing on analyzing statements, historical analysis and analysis of power. This article explains that Foucauldian discourse analysis is not textual-linguistic analysis, then it could be done in all of the research areas within communication studies, including communications research with managerial perspectives such as public relations, business communication, advertising, and others.